Pasintabi at babala content and trigger warnings in Philippine television news. - Villamiel, Vonn Andrei E.
Sensitive news reports, such as those containing themes of violence, trauma, and death, remain staples of Philippine television news. However, the mechanisms to alert viewers to such content are inconsistently applied. This study investigates the use of content and trigger warnings in primetime newscasts and the newsroom policies regarding their implementation. Guided by the Social Responsibility Theory of the Press, the Input-Process-Output model, and the Media Systems Theory, the study combines content analysis of 90 episodes, encompassing over 500 news segments from 24 Oras, TV Patrol, and Frontline Pilipinas, with in-depth interviews with news producers and a clinical psychologist. The findings reveal that while newsrooms demonstrate ethical sensitivity, the issuance of trigger warnings remains inconsistent and infrequent, appearing in only 3.77% of reports identified as sensitive. These warnings mainly appear in news segments containing highly graphic themes like crimes, violence, and accidents, excluding equally sensitive but less graphic topics such as mental health and trauma. In the few examples recorded in the study, warnings appear as anchor lead-ins or text graphics such as “babala” or “pasintabi.” Newsroom policies and media standards on the use of content and trigger warnings are either absent or ambiguous, resulting in the use of warnings being largely dependent on newsroom habits, informal precedent, and individual editorial discretion.